2018
DOI: 10.1021/acs.analchem.7b05405
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Tris(2-carboxyethyl)phosphine at Pyrroloquinoline Quinone Modified Carbon Nanotube through Single Nanoparticle Collision

Abstract: Inspired by the addition-elimination catalytic mechanism of natural pyrroloquinoline quinone (PQQ) containing proteins, PQQ-modified hybrid nanomaterials have been increasingly developed recently as biomimetic heterogeneous electrocatalysts. However, up until now, no existing electrochemical approach was able to assess the intrinsic catalytic activity of PQQ sites, impeding the design of efficient PQQ-based electrocatalysts. Herein, in this work, we introduced a new method to calculate the turnover frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Previous investigation has demonstrated that a carbon-fiber ultramicroelectrode modified with PQQ–CNTs exhibits high catalytic activity toward the electrochemical oxidation of TCEP through single-nanoparticle collision [ 29 ]. We first attempted to record the electrochemical signal by the direct electron transfer reaction between PQQ–CNTs and the electrode ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous investigation has demonstrated that a carbon-fiber ultramicroelectrode modified with PQQ–CNTs exhibits high catalytic activity toward the electrochemical oxidation of TCEP through single-nanoparticle collision [ 29 ]. We first attempted to record the electrochemical signal by the direct electron transfer reaction between PQQ–CNTs and the electrode ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Addition of TCEP to the electrolyte solution induced a clear enhancement in the anodic current within the potential range of 0.2–0.6 V (curve b). Note that the sensor electrode without capture of PQQ–CNT-Ab 2 labels had no contribution to this reaction (curve c); thus, the enhancement of the anodic current in curve b can be attributed to the electrocatalytic oxidation of TCEP by PQQ–CNTs [ 29 ]. We also found that no significant signal enhancement was observed when the antibody–PQQ conjugate was used as the label instead of PQQ–CNT-Ab 2 for signal output, demonstrating that the signal was amplified by using CNTs to load large quantities of PQQ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations